Transcriptional regulation of TacL-mediated lipoteichoic acids biosynthesis by ComE during competence impacts pneumococcal transformation - Yao, Miao; Wang, Kun; Song, Guangming; Hu, Yumeng; Chen, Jiali; Li, Tingting; Liang, Longying; Wu, Jie; Xu, Hongmei; Wang, Libin; Zheng, Yuqiang; Zhang, Xuemei; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Competence development is essential for bacterial transformation since it enables bacteria to take up free DNA from the surrounding environment. The regulation of teichoic acid biosynthesis is tightly controlled during pneumococcal competence; however, the mechanism governing this regulation and its impact on transformation remains poorly understood. We demonstrated that a defect in lipoteichoic acid ligase (TacL) -mediated lipoteichoic acids (LTAs) biosynthesis was associated with impaired pneumococcal transformation. Using a fragment of tacL regulatory probe as bait in a DNA pulldown assay, we successfully identified several regulatory proteins, including ComE. Electrophoretic mobility shift assays revealed that phosphomimetic ComE, but not wild-type ComE, exhibited specific binding to the probe. DNase I footprinting assays revealed the specific binding sequences encompassing around 30 base pairs located 31 base pairs upstream from the start codon of tacL. Expression of tacL was found to be upregulated in the ΔcomE strain, and the addition of exogenous competence-stimulating peptide repressed the tacL transcription in the wild-type strain but not the ΔcomE mutant, indicating that ComE exerted a negative regulatory effect on the transcription of tacL. Mutation in the JH2 region of tacL upstream regulatory sequence led to increased LTAs abundance and displayed higher transformation efficiency. Collectively, our work identified the regulatory mechanisms that control LTAs biosynthesis during competence and thereby unveiled a repression mechanism underlying pneumococcal transformation.